Additive manufacturing: Digitally changing the global business landscape - Christina Öberg (European Journal of Management and Business Economics (EJM&BE), 2019)
Purpose Additive manufacturing, that is, layer-based manufacturing technologies, is thought to change supply chain operations from global to local, while also affecting design processes and product structures. As this transformation happens, a power struggle among various actors relating themselves to additive manufacturing has emerged. The purpose of this paper is to discuss and explain the development of additive manufacturing from a power dependence point of view. Design/methodology/approach The paper is based on data collected from a number of seminars hosting a total of 620 industry experts representing 102 companies in the area, and reflecting every step of the supply chain. Findings The paper points out how measures to deal and create power imbalances occur also related to indirect parties, and how the disruptive character of the supply chain leads to exercised power. Originality/value The power struggle provides new insights into how an emerging technology is realised and the effect of protectionism on such attempts. Specifically related to additive manufacturing, the paper illustrates the business side from various actors' point of view, which adds to technological perspectives on additive manufacturing, as well as studies viewing the supply chain from a bird's-eye perspective.
Keywords: 650; Power; 3D printing; Supply chain